Understanding the role of facets and twin defects in the optical performance of GaAs nanowires for laser applications. Issue 7 (17th May 2021) - Azimi, Zahra; Gagrani, Nikita; Qu, Jiangtao; Lem, Olivier L. C.; Mokkapati, Sudha; Cairney, Julie M.; Zheng, Rongkun; Tan, Hark Hoe; Jagadish, Chennupati; Wong-Leung, Jennifer
Abstract : GaAs nanowires are regarded as promising building blocks of future optoelectronic devices. Abstract : GaAs nanowires are regarded as promising building blocks of future optoelectronic devices. Despite progress, the growth of high optical quality GaAs nanowires is a standing challenge. Understanding the role of twin defects and nanowire facets on the optical emission and minority carrier lifetime of GaAs nanowires is key for the engineering of their optoelectronic properties. Here, we present new insights into the microstructural parameters controlling the optical properties of GaAs nanowires, grown via selective-area metal–organic vapor-phase epitaxy. We observe that these GaAs nanowires have a twinned zinc blende crystal structure with taper-free 110 side facets that result in an ultra-low surface recombination velocity of 3.5 × 10 4 cm s −1 . This is an order of magnitude lower than that reported for defect-free GaAs nanowires grown by the vapor–liquid–solid technique. Using time-resolved photoluminescence and cathodoluminescence measurements, we untangle the local correlation between structural and optical properties demonstrating the superior role of the side facets in determining recombination rates over that played by twin defects. The low surface recombination velocity of these taper-free 110 side facets enable us to demonstrate, for the first time, low-temperature lasing from bare (unpassivated) GaAs nanowires, and also efficient room-temperature lasing after passivation with an AlGaAs shell.